2021
DOI: 10.1088/1361-6668/ac0b2d
|View full text |Cite
|
Sign up to set email alerts
|

Screening-current-induced mechanical strains in REBCO insert coils

Abstract: In recent years, remarkable progresses have been made in the R&D efforts for high temperature superconducting (HTS) high-field magnets. The screening-current-induced magnetic field and mechanical stress/strain in rare-earth barium-copper-oxide (REBCO) coils are raising growing concerns. This paper presents experimental and theoretical analyses on the effects of screening-current-induced mechanical strains in a REBCO insert setup without transport currents. Strain measurements on two REBCO coils, with and witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
52
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 37 publications
(50 reference statements)
3
52
0
Order By: Relevance
“…In the coupled model, the electromagnetic field distribution and mechanical deformation of HTS coil can be calculated simultaneously, meaning the interaction of the electromagnetic and mechanical responses can be considered. By considering the tilting angles of the deformed HTS tapes and the strain dependency of critical current [42,43], the result of the coupled model is more consistent with the experimental data. Afterward, Niu et al calculated the influence of the nonuniform distribution of critical current of HTS tapes on the electromagnetic and mechanical characteristics of HTS pancake coils based on the 3D coupled model [44].…”
Section: Introductionsupporting
confidence: 65%
See 1 more Smart Citation
“…In the coupled model, the electromagnetic field distribution and mechanical deformation of HTS coil can be calculated simultaneously, meaning the interaction of the electromagnetic and mechanical responses can be considered. By considering the tilting angles of the deformed HTS tapes and the strain dependency of critical current [42,43], the result of the coupled model is more consistent with the experimental data. Afterward, Niu et al calculated the influence of the nonuniform distribution of critical current of HTS tapes on the electromagnetic and mechanical characteristics of HTS pancake coils based on the 3D coupled model [44].…”
Section: Introductionsupporting
confidence: 65%
“…The influence of deformation of the HTS coil on the critical current density and electromagnetic field distribution is neglected in the uncoupled model. Kolb-Bond et al and Yan et al proposed the coupled electromagnetic-mechanical model, which takes into account the effect of mechanical strain [42,43]. In the coupled model, the electromagnetic field distribution and mechanical deformation of HTS coil can be calculated simultaneously, meaning the interaction of the electromagnetic and mechanical responses can be considered.…”
Section: Introductionmentioning
confidence: 99%
“…Ueda evaluates the electromagnetic force and stress due to the screening current by using the developed numerical simulation code [30]. Yan studies screening-current-induced mechanical strains in HTS insert coils [31,32]. The effect of the changing rotation angle of the conductor on the electromagnetic and stress state is investigated [33].…”
Section: Introductionmentioning
confidence: 99%
“…The use of an over-banding build at the outermost turn, wound with materials with a high modulus of elasticity, shares similar effects [2]. In dry-wound REBCO coils, it is shown that stresses in the superconducting winding can be reduced by adjusting the size and winding tension of the over-banding build [18][19][20][21][22]. In practice, thin stainless-steel (SS) tapes are often chosen considering its commercial availability and high modulus of elasticity.…”
Section: Introductionmentioning
confidence: 99%